Communicative Language Teaching (CLT) through Synchronous Online Teaching in English Language Preservice Teacher Education - Chiew Hong Ng (Cranmore Publishing, 2020)
This article deals with the challenges in training English language preservice teachers in the Communicative Language Teaching (CLT) approach through adopting synchronous online teaching using Zoom and the development of CLT tasks in the time of COVID-19. It outlines the teaching context, explains the rationale for training preservice teachers in the CLT Approach and the challenges of adopting CLT with distancing pedagogic practices where face-to-face sessions were not possible. It first examines the challenges of using synchronous online learning before explaining the rationale for adopting Zoom to train preservice teachers. It then describes how training was carried out, discusses the outcomes of the training and reflects on the practice of using synchronous online activities for training preservice teachers in the CLT Approach. The article concludes with teaching implications for educators looking at training preservice teachers in the CLT Approach through synchronous Zoom.